'Caecibacter massiliensis' gen. nov., sp. nov., isolated from human right colon. (May 2017) - Ricaboni, D.; Mailhe, M.; Benezech, A.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of 'Caecibacter massiliensis' strain Marseille-P-2974 T (CSUR P2974), which was isolated from a human right colon sample.